Ø§Ù„ØªØ§Ø±ÙŠØ® Ø§Ù„Ø¹Ù‚Ø¯ÙŠ ÙÙŠ Ø§Ù„Ù…Ø°Ù‡Ø¨ Ø§Ù„Ø´Ø§ÙØ¹ÙŠ - Salahuddin Guntung Raden (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2020)
This study aims to reveal the various patterns of belief in the internal of the Shafi'i school and also to explain the history of the emergence of these various forms of understanding after the early development of the Shafi'i school which is oriented towards pure salafi Sunni understanding. This research used the deductive inductive method. The results of this study show that the Shafi'i school as it develops in the aspect of fiqh through the hands of its figures, it also develops in the aspects of aqidah with quite rapid development. The Shafi'i school is no longer pure as it was in the days of its founder, Imam Al-Shafi'i, and his early figures. In the internal of the Shafi'i School, various forms of belief emerged which later became many different madrasas. Each madrasah produces a variety of views that are similar and are bound by the same ushul (principle) and their figures are connected with similar thoughts. The Shafi'i school was originally a pure Sunni school and could be called the Madrasah Syafi'iyyah Ahlussnnah. Then within the school, there appeared various types of understanding of the people of Kalam and Sufi. Then it became several madrasas with different styles of understanding. Within the schools, the concept of Kullabiyah Asy'ariyah emerged in the third century of hijriyyah where in the same century the people of Kalam and Sufi also emerged. Then in the fifth century, the concept of Asy'ariyah Muktazilah emerged. Then the concept of understanding of the Asy'ariyah Falsafi emerged and became grounded in the Shafi'i School in the sixth century of hijriyyah during the emergence of the concept of Kuburiyah which has survived to this day. However, the pure Sunni Salafi style remains in the internal Shafi'i school.